SNAP-25 Single Nucleotide Polymorphisms, Brain Morphology and Intelligence in Children With Borderline Intellectual Functioning: A Mediation Analysis - Blasi, Valeria; Bolognesi, Elisabetta; Ricci, Cristian; Baglio, Gisella; Zanzottera, Milena; Canevini, Maria Paola; Walder, Mauro; Cabinio, Monia; Zanette, Michela; Baglio, Francesca; Clerici, Mario; Guerini, Franca Rosa (Frontiers in Neuroscience, 2021)
Borderline intellectual functioning (BIF) is a multifactorial condition in which both genetic and environmental factors are likely to contribute to the clinical outcome. Abnormal cortical development and lower IQ scores were shown to be correlated in BIF children, but the genetic components of this condition and their possible connection with intelligence and brain morphology have never been investigated in BIF. The synaptosomal-associated protein of 25 kD (SNAP-25) is involved in synaptic plasticity, neural maturation, and neurotransmission, affecting intellectual functioning. We investigated SNAP-25 polymorphisms in BIF and correlated such polymorphisms with intelligence and cortical thickness, using socioeconomic status and environmental stress as covariates as a good proxy of the variables that determine intellectual abilities. Thirty-three children with a diagnosis of BIF were enrolled in the study. SNAP-25 polymorphisms rs363050, rs363039, rs363043, rs3746544, and rs1051312 were analyzed by genotyping; cortical thickness was studied by MRI; intelligence was measured using the WISC-III/IV subscales; environmental stressors playing a role in neuropsychiatric development were considered as covariate factors. Results showed that BIF children carrying the rs363043(T) minor allele represented by (CT+TT) genotypes were characterized by lower performance Perceptual Reasoning Index and lower full-scale IQ scores (p=0.04) compared to those carrying the (CC) genotype. This association was correlated with a reduced thickness of the left inferior parietal cortex (direct effect =0.44) and of the left supramarginal gyrus (direct effect =0.56). These results suggest a link between SNAP-25 polymorphism and intelligencewith the mediation role of brain morphological features in children with BIF.